Development and heritability of subcortical brain volumes at ages 9 and 12. (30th October 2014) - Swagerman, S. C.; Brouwer, R. M.; de Geus, E. J. C.; Hulshoff Pol, H. E.; Boomsma, D. I.
<x xml:space="preserve">Abstract</x> Subcortical brain structures are involved in a variety of cognitive and emotional functions and follow different trajectories of increase and decrease in volume from childhood to adulthood. The heritability of development of subcortical brain volumes during adolescence has not been studied comprehensively. In a longitudinal twin study, we estimated to what extent subcortical brain volumes are influenced by genetic factors at ages 9 and 12. In addition, we assessed whether new genes are expressed at age 12 and whether there is evidence for genotype by sex interaction. Brain scans were acquired for 112 and 89 twin pairs at 9 and 12 years of age. In both boys and girls, there was an increase in volumes of the thalamus, hippocampus, amygdala and pallidum, and a decrease in volumes of the caudate and nucleus accumbens. The putamen showed a decrease in boys bilaterally and an increase in girls in the left hemisphere. Heritability was high (>50%) for all structures – except for the left nucleus accumbens – with heritabilities ranging from 0.50 to 0.91 at age 9, and from 0.59 to 0.88 at age 12. There were no significant new genetic effects coming into play at age 12, and there was no evidence for genotype by sex interactions. These findings suggest that despite their sensitivity to environmental effects, the heritability of subcortical brain structures is high from childhood on, resembling estimates found in adult samples.